Pemerolehan Bahasa Inggris pada Anak Berbahasa Indonesia Melalui Tayangan Lagu-Lagu di Akun YouTube Terpilih - Indra, Deden; Ambarwati, Ari (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
YouTube plays a crucial role in early childhood language acquisition by offering interactive and engaging educational content, allowing children to learn language through songs, stories, and supportive visuals. Regular exposure to foreign languages through YouTube videos accelerates their understanding and natural use of the language in everyday contexts. This study aims to provide a detailed and comprehensive explanation of the process and outcomes of second language acquisition in toddlers whose first language is Indonesian, and who are exposed to English-language songs from YouTube channels. The method used in this study is Narrative Inquiry, which aims to provide a depiction of lived experiences, capturing the complexity and situational context from the internal perspective of the research subjects. The findings indicate that exposure to educational content does not entirely have detrimental effects. In the context of this research, the subject successfully acquired a second language through YouTube videos introduced at the age of 13 months. By the time the subject reached 27 months, observations showed that the subject had successfully acquired more than 17 vocabulary words that could be used appropriately in context. This study highlights that toddlers exposed to YouTube content can experience positive effects in second language acquisition, with various vocabulary words absorbed during the critical period of language learning. Therefore, content focused on educational material, such as Toddler Learning Videos and songs for children, is recommended as a method of language acquisition therapy for children. Educational works by Rachel and Aron, notably on the Ms. Rachel channel, or productions from the Blippi YouTube channel developed by Stevin W. John, have been proven to have a significant positive impact.